I think learning ancient Greek via video game is…’: An online survey to understand perceptions of Digital Game-Based Learning for ancient Greek - Irene Di Gioia (The Journal of Classics Teaching, 2024)
Playing is connected at a deep level to how we learn, participate in and create culture, as it is dynamic, complex and even unpredictable just as learning is (Reinhardt, 2019). Even Plato in his Theaetetus recognises the importance of such a component in experiencing culture and knowledge. Could playing (or gaming) therefore be a useful didactical approach in promoting the study of ancient Greek around the world? From 10th May 2023 at 1 pm. until 1st June 2023 at 1 pm., an internet survey was conducted online by the researcher Irene Di Gioia through the use of Google Forms questionnaires. This questionnaire was distributed via different social networks and communication tools. The survey aimed to understand if people around the world are interested in the idea of learning ancient Greek via a video game and if so, which video gaming activities learners prefer. The goal of the survey was therefore to understand if a ludic pedagogical approach using Digital Game-Based Learning could theoretically represent an interest experience for learners or potential learners, and furthermore to investigate their feelings, prejudices, and motivations regarding the study of ancient Greek. From the analysed data the researcher will therefore develop a video game to teach ancient Greek language and culture, which comprises the focus of her ongoing PhD dissertation at Georg-August University of Göttingen (Germany) and Alma Mater Studiorum University of Bologna (Italy).